Nutrition and dietary supplements in the prevention of osteoarthritis - Vidović Bojana; Đorđević Brižita (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2016)
Optimally balanced diet in order to body weight control in combination with adequate physical activity has an important role in the prevention of degenerative joint disorders. Weight reduction is important in ameliorating some of the manifestations of osteoarthritis (OA) and improving the quality of life. There is growing interest in the beneficial effects of some nutrients, especially polyunsaturated fatty acids and vitamin D, as well as many non-nutrient biological active compounds on progression structural damages, pain and functions of the joints. Glucosamine, chondroitin sulfate, S-adenosylmethionine, methylsulfonylmethane, alone or in combination, are among the most widely used dietary supplements for the prevention and treatment of OA. However, there are limited high-quality designed clinical trials which supported its potential symptomatic and structure-modifying effects.